Application of local loads in aerobic exercises during preparation of sprint swimmers - Popov, G.; Alatortsev, S.; Kochergin, A. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. II, 2008)
Introduction The preparatory periods during the preparation of high class sprint swimmers are characterized by the application of a significant volume of aerobic exercises. This may neglect the need for exercises which are characterized by speed and strength, which are consistent with the requirements for sprint swimming. The exercises which are generally performed on land may also be deficient with respect to the qualities of sport and force required during the event and performance in the water. At the same time, in practice examples of development of speed-strength qualities directly in special - preparatory exercises of a concrete kind of sports are known. For this purpose local loads, placed on lower limbs of an athlete`s body by means of what dosed out force influence on concrete muscular groups in conditions when the biomechanical structure of movements comes nearer to structure of competitive exercise is carried out are used.The purpose of the research was to identify appropriate exercise loads and characteristics to be used in the preparation of a high class sprint swimmers during the earlier stage of the year using aerobic exercise in the water. Methods Local loads were focused around the limbs centers of mass, and the magnitude of the loads did not exceed 10 % of the weight of the segment. The study involved a group of highly skilled sprint swimmers. They carried out aerobic exercises for a period ranging from 3 to 40 minutes with local loads placed on the forearms, shoulders, or both .Measurements were obtained by means of biomechanical video recording of kinematic parameters such as speed distance, rate and a step length and also tests of blood lactate Results / Discussion With an emphasis on local loads at the shoulder the training effect was minimal. There was a relative increase in the step` length - the least, in comparison with other variants of an arrangement of local loads, thus are marked rather small values laktat in blood (2 - 2.5 mmol/l). Loading of the forearm showed and average increase in the relative step length and the average values for blood lactate in blood (3.5 - 3.8 / ). The combined use of local loads on the shoulders and forearms allowed the greatest relative increase in the length values of a step, due to increase in a the blood lactate parameter (5.7 ± 0.4 / ). For comparison use of the "Biokinetik" simulator on land by the same swimmers at training load of approximately identical intensity and volume was accompanied by an increase in blood lactate of the swimmers up to 9 - 11 mmol/l. Conclusions Use of local loads in the preparation of sprint swimmers expediently, at the preparatory stage of the year provides a differentiated influence on the activity of the basic muscular groups at a relatively reduced metabolic cost in comparison with land exercises emphasizing the standard methods of developing speed and strength.